BORA-dependent PLK1 regulation: A new weapon for cancer therapy?. (2nd September 2016) - Cirillo, Luca; Thomas, Yann; Pintard, Lionel; Gotta, Monica
ABSTRACT: The mitotic kinase polo like kinase 1 (PLK1) is overexpressed in many cancers and its inhibition slows down proliferation and increases apoptosis in cancer cell lines. Understanding how PLK1 is activated is therefore crucial for the development of novel PLK1 inhibitors with anticancer properties. We recently identified a conserved regulatory loop leading to PLK1 activation that involves cyclin-dependent kinase 1 (CDK1).